Investigation of the Power Quality Concerns of Input Current in Single-Phase Frequency Step-Down Converter - Naveed Ashraf; Ghulam Abbas; Nasim Ullah; Ahmad Aziz Al-Ahmadi; Ali Raza; Umar Farooq; Mohsin Jamil (Applied Sciences, 2022)
Single-phase direct frequency converters are gaining attraction at the research and academic level as they are rapidly getting space over conventional multistage converters. The converters developed with a rectification and inversion process using a DC-link level are examples of multistage converters with some serious concerns such as an increase in the overall weight, losses, and cost. They also suffer from the low-reliability issue due to the issues involved with DC-link capacitors and problems linked with electromagnetic interference (EMI) caused by high-frequency pulse width modulation (PWM) switching. These problems are addressed with line frequency switching cycloconverters. In these converters, the power quality of the output voltage is improved by governing the amplitude of some selected output pulses or half-cycles. For this purpose, a low-frequency multiple tapping transformer may be used to obtain various voltage levels. However, its use is the main source of increased overall weight, losses, cost, and volume. In transformer eliminated topologies, high-frequency PWM control can be employed to control the magnitude of some selected half cycles of the output voltage. However, this approach may arise some problems related to EMI. In both control techniques, the attention is focused on the power quality of the output voltage only. The concern for the input current is ignored and not yet analyzed. This is one of the critical power quality concerns and requires further investigation. The magnitude control of the output half-cycles causes the variation in the amplitude of some half cycles of the input currents. As a result, all half cycles of the input current become non-symmetric. It generates harmonics that are always of low frequency and cannot be easily filtered out. It results in a high value of the harmonic factor (HF) of the input current. The improvement in the power quality of the output voltages severally degrades the power quality of the input currents. In this research, this problem is investigated with mathematically computed harmonic coefficients with a pulse selective approach. Also, a simple single-phase cycloconverter is introduced to improve the power quality index of the input current. The overall analysis is supported by the results obtained from a Simulink-based environment and a practically constructed prototype.